2021
DOI: 10.7759/cureus.20289
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cancer Causes of Death in Patients With Pancreatic Adenocarcinoma: A Surveillance, Epidemiology, and End Results (SEER)-Based Study

Abstract: Background This study aimed to identify the most common causes of non-cancer mortality in patients with pancreatic adenocarcinoma (PAC) and compare their mortality risk with the general population. Methodology This study analyzed PAC patients’ data registered in the Surveillance, Epidemiology, and End Results (SEER) database. We studied the causes of death and investigated their association with age, sex, race, tumor stage at presentation, and treatment modality according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, these patients had a cardiac-speci c survival rate of 261 (84.6%) patients at 10 years and 9 (2.8%) patients at 15 years compared with an other-cause survival rate of 6793 (98.2%) patients at 10 years and 4712 patients (68.1%) at 15 years in a cohort study of a total of 7227 patients 9 . In a study of 67,694 pancreatic adenocarcinoma patients, Harvitkar et al illustrated that the percentage of heart disease accounted for the total number of all causes of death in the following time frames : less than 1 year (SMR : 3.17; 95% CI: 2.93-3.43), 1-5 years (SMR : 2.00; 95% CI: 1.72-2.32), 5-10 years (SMR : 2.65; 95% CI: 1.84-3.68), and more than 10 years (SMR : 2.05; 95% CI: 0.66-4.78) 10 . However, neither of these studies thoroughly illuminated cardiovascular disease mortality among patients with pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, these patients had a cardiac-speci c survival rate of 261 (84.6%) patients at 10 years and 9 (2.8%) patients at 15 years compared with an other-cause survival rate of 6793 (98.2%) patients at 10 years and 4712 patients (68.1%) at 15 years in a cohort study of a total of 7227 patients 9 . In a study of 67,694 pancreatic adenocarcinoma patients, Harvitkar et al illustrated that the percentage of heart disease accounted for the total number of all causes of death in the following time frames : less than 1 year (SMR : 3.17; 95% CI: 2.93-3.43), 1-5 years (SMR : 2.00; 95% CI: 1.72-2.32), 5-10 years (SMR : 2.65; 95% CI: 1.84-3.68), and more than 10 years (SMR : 2.05; 95% CI: 0.66-4.78) 10 . However, neither of these studies thoroughly illuminated cardiovascular disease mortality among patients with pancreatic cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these nding, there are few reports on cardiovascular disease among pancreatic cancer patients in the literature. Harvitkar et.al's descriptive study of 67,694 patients with pancreatic adenocarcinoma found that heat disease accounted for approximately 4% of non-cancer deaths, with an increasing trend from 1.27% in less than one year of follow-up, to 6.41% in more than ten years of follow-up 10 . Therefore, cardiovascular disease should not be overlooked as a cause of death among pancreatic cancer patients.…”
Section: Introductionmentioning
confidence: 99%